Zawartość semantyczna konceptu artystycznego „sakrament małżeństwa” w opowiadaniu I. Bunina „Wieś” - Królikiewicz, Natalia (Studia Rossica Posnaniensia, 2016)
To understand the semantic content of the creative concept of ‘’the sacrament of matrimony’’ in Ivan Bunin’s novel The Village, it is necessary to focus on revealing the semantic components of ‘’culture coagulate’’ (a term by J. Stepanov) and its artistic realization on various levels of the text. This analysis allows the author to indicate that opposites (such as death and birth, wedding and funeral, tragedy and farce) are united in a way that is typical for Bunin.